Characteristics and significance of running speed at the Australian Open 2006 for training and injury prevention - Weber, K.; Pieper, S.; Exler, T. (Medicine and Science in Tennis, 2007)
Background As an elementary prerequisite for organising an efficient training and optimal injury prevention programme, a differentiated analysis of the quality and quantity of running speed in competitive tennis is required. This analysis was taken from all the matches at the Men`s Australian Open 2006 from the quarter-final stages onwards.